Pengaruh Serbuk Batu Kapur di Daerah Semanding Tuban sebagai Variasi Bahan Substitusi Semen terhadap Nilai Slump - Tirani, Aksaradia Sang; Rochmah, Nurul (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
The massive use of concrete in the construction industry presents significant environmental challenges, particularly due to the high consumption of cement. Cement is a material that contributes substantially to global carbon dioxide (CO₂) emissions. According to data from the Chatham House Research Institute, global cement production in 2016 generated approximately 2.2 billion tons of CO₂, equivalent to 8% of total global carbon emissions. This condition indicates the need for efforts to increase efficiency in cement use through innovations in concrete mixtures, including the utilization of substitute materials such as limestone powder. This study aims to evaluate the slump values of concrete with various limestone powder substitution percentages using the Design of Experiment (DoE) method for mix design and the SNI 1972:2008 “Concrete Slump Test Method” as the testing standard. The analysis technique was carried out by measuring the height of fresh concrete before and after being placed into the Abram cone to obtain the slump value as an indicator of workability. The results show that the slump values for the 0%, 5%, 10%, 12.5%, 15%, and 35% variations were 18 cm, 16 cm, 15.75 cm, 11.5 cm, 12.5 cm, and 12 cm, respectively. The highest slump was obtained at the 0% variation, while the most optimal slump was found at the 12.5% variation with a value of 11.5 cm, as it lies within the ideal range—not too fluid, which risks segregation, and not too stiff, which complicates compaction. This study demonstrates that the addition of limestone powder at certain levels can significantly influence concrete workability.